Technical education and labor Market (Institutes of Duhok Governorate) - 2006-2010 - Abdelkader, Kalthoum; Albbhadir, Shafiq; Habib, Ahmed M. (Humanities Journal of University of Zakho, 2013)
Technical Educationis regarded as a way of preparing a work force for industry, then as a means to improve the formation of human capital and increase productivity and employment and it plays an essential role in economic development. More recently it has been seen as a tool to enhance human development by creating capabilities and putting them to use for further sustainable human development. The labour market is directly affected by the output of the educational process, especially by technical education.Recognizing its prominent role in economic and social development, technical education has received much attention and care by the Kurdistan Regional Government (KRG). It has been addressed as one of the most important instruments of national policies aimed at providing qualified human resources, reducing unemployment and alleviating poverty.One of the far reaching measures of these policies has been the establishment of 17 Technical Institutes throughout the Kurdistan Region, 5 of these in the Dohuk governorate alone. In 2010/2011, the number of teaching staff in all Technical Institutes in Erbil and Dohuk increased to 396, at the same time the number of student rose to 14,624 in the Erbil and Dohuk Technical Institutes. In 2007, the (KRG) spent US $ 164 million of its budget for the Ministry of Higher Education and Scientific Research (MOHESR) while in 2011 this amount increased to US $496 million. These Institutes are assigned with the utmost important developmental mission of promoting technical education in accordance with the needs of the labour market.Commentators maintain that these Institutes would lack a clear vision of the needs of the local labour market as they would fail to build a co-operative partnership with local employers to exchange information. Other critics go even further and argue that some departments at these Institutes were established and their curricula chosen according to the availability of teaching personnel without considering the needs of the local labourmarkets. Accordingly, it is often claimed that the poor performance of the Technical Institutes is the main reason for the lack of adequately educated technical personnel which could meet the requirements of the rapidly developing local businesses.This master thesis attempts to analyze and evaluate the performance of the technical education in the Governorate of Dohuk with special reference to the needs of the local labour market as the primary criterion of evaluation. The six Technical Institutes in the Governorate will be the focal point of analysis as they are by far the main providers of technical education.